The legal nature of the designation of the facility - Yassaad, Fadila (Journal of Human Sciences, 2021)
The Algerian legislator has given a concept of designation of origin through Ordinance No. 76-65 of July 16 related to appellations of origin. The designation of origin has taken natural and human factors as the basis for its concept. Legislation has differed in naming it, some of them are called the designation of the geographical indication and some of them He calls it the source data ... etc.All of these terms share one goal, which is to define the origin of a particular commodity that determines the quality and features of these commodities, and in order for this label to produce its legal effects, a set of formal and objective conditions must be met, the most important of which is the registration, which is its backbone